Modern Media Design: the Impact of Digital Technology on the Development of Regional Publications - Anatoljevna Sukhotina, Irina; Nikolaevna Ivanishcheva, Olga; Vjacheslavovna Koreneva, Anasstasija; Mihajlovna Shadrina, Irina; Vjacheslavovna Ashutova, Tatjana (International Journal of Engineering and Technology, 2018)
The article examines the principal laws of print design, such as communicativeness, usability and visual attractiveness, in terms of their current use in a modern urban regional newspaper. This paper also presents an analysis of "The Evening Murmansk" newspaper design (logo, photos, front page), along with experts' interviews and readers' polls. The relevance of the work is the unique regional material, as well as a special view on the regional media fate, presented by the perception that modern urban regional newspapers are understaffed with both technical and human resources to attract attention of readers, especially of young people.Â Â